Mouse inclusivo para idosos: desenvolvimento e avaliação de usabilidade - Rocha, Rosana Gonçales Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
O presente estudo trata do desenvolvimento de um mouse específico para idosos buscando atender às necessidades desse público em relação a usabilidade e desempenho considerando os declínios e as debilidades motoras decorrentes do envelhecimento. O modelo proposto, em forma de protótipo, foi avaliado em conjunto com outros quatro modelos de mouse, sendo um padrão, dois ergonômicos verticais e um ergonômico horizontal, por meio de testes de coleta e análise de dados de performance (tempo X número de erros), percepção e usabilidade (agradabilidade, estética, complexidade), antropometria das mãos, avaliação socioeconômica e de caracterização da amostra composta de 40 sujeitos, divididos em dois grupos distintos: Grupo de Idosos Experientes (GIE): foram incluídos neste grupo idosos (acima de 60 anos) que estavam adaptados ao uso do computador de mesa e mouse, n=20; Grupo de Idosos Inexperientes (GII): foram incluídos neste grupo idosos (acima de 60 anos) que não tinham nenhuma experiência com o uso de computador de mesa e mouse, n=20. Após a coleta de dados, três idosos do GIE e um idoso do GII foram descartados por não conseguirem concluir a tarefa. Os resultados mostraram que diferentes tipos de mouse interferem no uso e na percepção, bem como o grupo com menores dimensões na mão obteve melhores resultados em relação ao tempo de movimento, ainda que em relação ao número de erros a diferença não tenha sido relevante. Embora com um baixo ângulo de extensão de punho, o que mantém uma posição neutra, o protótipo apresentou problemas de execução do projeto, o que comprometeu a maior parte dos resultados, sendo rejeitado pela maior parte dos idosos. Mesmo assim, o estudo mostrou que um dispositivo desenvolvido especificamente para idosos pode melhorar o uso e aumentar a satisfação.

The present study addresses the development of a specific mouse for the elderly seeking to meet the needs of this public regarding usability and performance considering the declines and motor weaknesses resulting from aging. A prototype of the proposed model was evaluated along with four other mouse models, being one standard, two vertical ergonomic and one horizontal ergonomic by means of performance tests – Fitts’ Law test – (time X number of errors), perception and usability (pleasantness, aesthetics, complexity). The sample consisted of 40 subjects divided into two distinct groups: a) Experienced Elderly Group (EEG, n=17); b) Inexperienced Elderly Group (IEG, n=19) who had some or no experience using a desktop and mouse respectively. Results showed the prototype made a positive difference in the average wrist extension angle well below the second best average angle among the other tested models. The results obtained using Fitts’ Law test showed that the proposed mouse model interferes in selection time, movement time and number of errors, considering the mouse design, format, and dimensions. Problems to execute the prototype mouse project, mainly its weight and button which was difficult to click, affected its use and results, causing its performance to be low during its use in both elderly groups (EEG and IEG). There was an exception regarding movement time in the EEG group, where the prototype obtained an average time below one of the models and very close to the time of the other tested models. The study also showed that different types of mouse interfere in the perception too – in this regard, the problems with the prototype again affected the results. Although the prototype has been considered the most comfortable to accommodate the hands in spontaneous reports, it was considered unpleasant, difficult to use and poor aesthetically. The fact that the prototype featured a single-click button was considered a positive factor according to the reports by most of the inexperienced elderly subjects. This makes it evident that a device specifically developed for the elderly can improve its use and increase satisfaction when a mouse is used and consequently its use in the computer. The result was not conclusive due to problems with the prototype’s execution.
Ergonomic mouse for the elderly: development and assessment of usability
Keywords: Idosos; Inclusão digital; Mouse; Design ergonômico; Design inclusivo; Inovação frugal; Elderly; Digital inclusion; Ergonomic design; Inclusive design; Frugal innovation